Meta Analysis of Therapeutic Effect of Jichuan Decoction Combined with Acupuncture and Moxibustion for Functional Constipation - Haibing QIN; Aiyuan ZOU; Lianhuan YANG; Zhaotian WU (康复学报)
Objective:To evaluate the efficacy of Jichuan decoction combined with acupuncture and moxibustion in the treatment of functional constipation, and provide necessary reference for clinical treatment.Methods:Two independent researchers electronically searched databases, including VIP Database (VIP), Wanfang Database, China Knowledge Network Database (CNKI), China's Traditional Chinese Medicine Database, China Biomedical Literature Database (CBM), Embase, PubMed and Clinicalkey, to collect randomized controlled trials (RCTs) about functional constipation treated by acupuncture and moxibustion from the establishment time of the library to December 31, 2018. Then the two researchers independently conducted literature screening, basic data extraction and bias risk assessment. Jadad scale was used to evaluate the literature quality (score of 1-3 was considered as low quality, and score of 4-7 was considered as high quality), and data was extracted and evaluated by RevMan 5.3 software, which was used for Meta-analysis.Results:A total of 8 RCTs were enrolled, including 574 cases. Meta-analysis showed that the effective rate of Jichuan decoction combined with acupuncture and moxibustion[OR=3.59, 95%CI(1.37, 9.39), P< 0.01]and the cure rate[OR=4.31, 95%CI(2.92, 6.37), P< 0.01]were significantly higher than those of other drugs only, including Jichuan decoction, Chinese medicine preparation of hemp kernel, Cisapride tablets. Among 8 RCTs, adverse reactions were mentioned in two literatures, and there was only one literature which detected safety indexes. The results indicated that both the treatment group and the control group had normal safety indexes, and no adverse reactions were reported in all literatures. The Jadad scale score was 2-3 points, and the quality of all of literatures included in the study was low. The inverted funnel plot analysis of the included studies with the effective rate as the index showed that there was incomplete symmetry, suggesting that there might be publication bias in the research literature.Conclusion:Jichuan decoction combined with acupuncture and moxibustion can improve effectively the TCM symptoms of patients with functional constipation, and the effect is better than using other drugs only, including Jichuan decoction, Chinese medicine preparation of hemp kernel, Cisapride tablets. However, it is still necessary to expand the sample size and improve the research quality, so as to design more rigorous randomized controlled trials to verify the above conclusions.